Cis- and trans-9, 10-di(1H-imidazol-1-yl)-anthracene based coordination polymers of ZnII and CdII: synthesis, crystal structures and luminescence properties. Issue 2 (14th December 2017) - Vasylevskyi, Serhii I.; Regeta, Khrystyna; Ruggi, Albert; Petoud, Stéphane; Piguet, Claude; Fromm, Katharina M.
Abstract : New luminescent coordination polymers of anthracene with Zn II and Cd II were developed for detection of traces of nitro explosives. Abstract : New functional coordination polymers based on the semi-flexible 9, 10-di(1 H -imidazol-1-yl)-anthracene ligand (L ) with Zn II and Cd II, namely {[Zn(μ2 -L )2 ](ClO4 )2 · m (MeOH)· n (DCM)} n (1 ), {[Zn(μ2 -L )2 ](BF4 )2 · m (MeOH)· n (DCM)} n (2 ), {[Zn(μ2 -L )2 ( p -Tos)2 ]· m (DCM)· n (MeOH)} n (3 ), {[Cd(μ2 -L )2 ( p -Tos)2 ]· m (DCM)} n (4 ) {[Cd(μ2 -L )2 ( p -Tos)2 ]· m (MeOH)· n (Dioxane)} n (5 ) and {[Zn(μ2 -L )2 (CF3 CO2 )2 ]·2(Dioxane)} n (6 ), were obtained. DissolvingL in polar solvent mixtures MeOH–DCM (4 : 1) or MeOH–dioxane (1 : 1) with Zn II and Cd II salts resulted in the formation of complexes1, 2, and5 adopting a cis -conformation of the imidazole groups with respect to anthracene. In less polar mixtures of solvents such as MeOH–DCM (1 : 4) trans -L is observed, leading to the coordination polymers3–4 with Zn II and Cd II . In an intermediate solvent mixture such as MeOH–dioxane (1 : 4), the cis - and trans -conformation coexist as exemplified in complex6 with Zn II . In the solid state, complexes1–5 assemble as supramolecular 2-D coordination polymers with a ( 4, 4 ) topology, while6 forms a tridimensional porous network with a cds topology. All compounds reveal strong blue emission in the solid state at room temperature.